Holocentric chromosomes in animals and plants: what do we know about these points outside the curve? - Corrêa Morais, Gabriela (2023)
Usually, members of the Eukarya domain have kinetochores grouped at a single point, characterizing monocentric chromosomes. However, in some taxa the protein apparatus that composes the kinetochore is distributed continuously or discretely along the length of the chromosome, condition that defines holocentric chromosomes. The review aims to provide an overview of karyomorphological aspects of holocentric chromosomes in animals and plants, as well as an understanding of their origin, evolution and possible adaptive implications of their presence in eukaryotes. The main structural differences between holocentric and monocentric chromosomes concern the kinetochore proteins, the pattern of histone H3 phosphorylation and centromeric satellite DNA. The distribution of holocentric chromosomes in phylogenetic trees evidence their independent emergence numerous times throughout evolution. While many hypotheses have been created to explain the origin of holocentric chromosomes, none have been confirmed or refuted. Although the adaptive advantages generated by their presence are undeniable, especially in clastogenic environments, the typical behavior of chromosomes with diffuse kinetochores seems to be enough to make them the exception rather than the rule among eukaryotes.